WHAT IS THE IMPACT OF CIRCULAR ECONOMY IMPLEMENTATION ON COUNTRY’S WEALTH IN THE EUROPEAN UNION 27 COUNTRIES? : AN EMPIRICAL STUDY WITH EUROSTAT DATA - Almayzhar, Hauzaan (PEOPLE: International Journal of Social Sciences, 2024)
Circular Economy is considered to be the most appropriate approach to achieve a sustained economy in a sustainable way. Although many scholars have investigated the impact of circular economy implementation on how it will contribute to a country’s economy the results are still vague. To examine the relationship of Circular Economy and its impact towards a country’s wealth I performed a multiple linear regression on 27 European Union countries and the findings revealed a significant correlation between circular economy adaptation and the contribution to wealth in the countries. The findings implicate how policy makers could adopt a circular economy and achieve a sustainable economy.